News at the Bell and a Level Playing Field - Hu, Danqi; Stephan, Andrew (The Accounting Review, 2022)
ABSTRACT We provide initial evidence that stock exchange procedures around closing auctions advantage speed traders at the expense of auction participants. We show that, on Nasdaq and NYSE Arca, 4:00 pm earnings releases result in informed trading in the continuous regular-hour session in the short window between 4:00 pm and the closing auction; this trading subsequently moves closing prices in the direction of the earnings news. The ability of speed traders to submit 4:00-pm-news orders to the auction through the continuous session earns them up to 1.5 percent profit and creates an unlevel playing field because most auction participants are not allowed to cancel their orders. When stock exchanges recommended that firms delay disclosures until after the market closes, those with higher institutional ownership were more likely to voluntarily do so. Our study has implications regarding the timing of information releases and the design of the closing process.